Bentuk Pemberian Hukuman Dalam Pendidikan Islam - Wibawati Bermi (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2019)
Among the forms of punishment that are often used in the teaching and learning process is by giving penalties to students, both preventive and repressive. The existence of this punishment is expected to be able to prevent various violations of the regulations that have been made, besides that the punishment is also a form of stern warning arising from fear of threats. Punishment is an educational measurement tool for the functional quality of education for students who have problems and students who excel. Punishment is an early prevention in the context of educating those who are problematic. Punishment is something that is recommended and is one of the means of successful education, and needs to be done occasionally by an educator. Punishment in education has a function as a tool to motivate and enhance student learning. Punishment is also a reward for a bad deed. Punishment given to students must be carried out appropriately and can be carried out. In giving a sentence must be based on the form of punishment carried out by the Prophet Muhammad contained in the Hadith. Keywords: method, punishment, preventive, refressive.